(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research is based on the study of the concept of deletion exhibitor, which is a departure from the familiar format of the language; The content of this study was based on two main approaches: the first is to explain the concept of the exhibitor and deletion and clarify them as contained in the lexicons of the language; It aims to demonstrate the semantic effect of deletion in the poetry of Abu Tammam at the level of the nominal sentence through the novice and the news first, and the actual through the verb and the second.